On Some New Hermite-Hadamard Type Inequalities for s-Geometrically Convex Functions - İmdat İşcan (International Journal of Mathematics and Mathematical Sciences)
Some new integral inequalities of Hermite-Hadamard type related to the s-geometrically convex functions are established and some applications to special means of positive real numbers are also given.